EMOTIONAL OUTLINE OF THE STUDENTS IN CLINICAL PRACTICE. TUTORIAL ACTION IN NURSING FOR SUPPORT, FORMATION, DEVELOPMENT AND CONTROL OF THE EMOTIONS - Sanjuán Quiles, Ángela; Ferrer Hernández, María Elena (Investigación y Educación en Enfermería, 2009)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Education of emotional intelligence and promotion the evolutive and socioemotional development of medical students is necessary in the educational ambit. Universities are evaluated for their quality in terms of knowledge and technical training, paying less attention to the acquisition of values, behavior, personal and professional attitudes. Objective: Know the emotional profile of the students in clinical practice and their relationship with learning (efficiency). Methodology: Graphic exploratory study, transversal, with activities to find emotional responses of nursing students in the clinical learning. Evaluate knowledge through the Spanish modified trait meta-mood scale – 24 (TMMS-24), with self reports, external observation and tutorials. The sample (N=100) is formed by all nursing students allocated in Elda’s Hospital (Alicante-Spain). The study was conducted in 2005/2006 and 2006/2007. Results: The tally suggests solutions to correct attention, clarity, and emotional reparation. The percentage of improvement is found for men and women in the areas of Attention and Emotional clarity by 30%, being the necessity of improvement the reparation in women of the 32.14% and 37.5% in men. The difference is in how the students are perceived in the team’s relationships and how they are observed by professionals. In the tutorial sessions they express different feelings related with professionals or patients, fear, emotions, insecurity, sadness, impotence, anger, and marginalization. Conclusions: Students with needs in control and emotional handling perceived negatively their environment during clinical practices and support received.